Exploration of Physics-Chemical Quality Lahor Reservoir of Malang District, Indonesia - Hery Setyobudiarso; Endro Yuwono (Widyagama University of Malang, 2018)
Lahor Reservoir was built and functioned as a water provider for agricultural activities, flood control, electricity generation, tourism activities and inland fisheries. This reservoir is one of the inflows of the Sutami reservoir which is the largest reservoir in East Java. This Lahor Reservoir is drained by three rivers, namely the Lahor River, Leso River and the Dewi River, which flows through housing and paddy fields, allowing the entry of organic and inorganic materials from various activities around the rivers and reservoirs. The aim of the study was to assess the physico-chemical parameters of the Lahor reservoir during the dry season. This research was conducted between March and April 2018. Water quality analysis was carried out in the Laboratory of Environmental Engineering Department of ITN Malang. The study was conducted by survey method and sampling method. Measurement of physical and chemical parameters of the waters was determined at 4 stations and each station consisted of 5 sampling points with different depths. Data analysis using descriptive statistics (mean, graph). The assessment of the temperature in the waters of the Lahor Dam ranged from a value of 24-28o C, turbidity with a value of 0.4 NTU, DO values from surface to base increased significantly with values of 29.1 mg / L, 33.9 mg / L and 34.3 mg / L and still meet the minimum water requirements for aquaculture. The high BOD value at the Lahor reservoir outlet is influenced by the accumulation of organic substances from several inlets and dam waters. Phosphate values are higher along with water depth and Fecal Coli ranges from 1-2 MPN / 100 mL at all sampling points. In general, the Lahor reservoir water still meets the quality standards for class I waters.